Peutz-Jeghers Syndrome - Mahendra, Cipta (PT. Kalbe Farma Tbk., 2021)
Sindrom Peutz-Jeghers (Peutz-Jeghers Syndrome/PJS) merupakan penyakit herediter langka dengan ciri klinis pigmentasi mukokutaneus dan polip gastrointestinal. Hingga kini, satu-satunya upaya terapi adalah eliminasi polip melalui metode endoskopi dan/atau operasi laparatomi abdomen invasif. Penderita PJS memiliki risiko tinggi mendapat berbagai jenis kanker sehingga diperlukan skrining rutin. Para penderita PJS perlu mendapat edukasi dan dukungan mental. Diperlukan riset lebih mendalam untuk tatalaksana terbaik sindrom PJS.Peutz-Jeghers Syndrome (PJS) is rare hereditary disease with mucocutaneous pigmentations and gastrointestinal polyps as the most prominent clinical features. The only approved treatment is to eliminate the polyps by endoscopy and/or invasive abdominal laparotomy surgery. Patients with PJS have a high lifetime risk of various cancers and warrants regular surveillance for early signs of malignancies. PJS patients need to be well-informed and supported by the treating physicians to cope with their PJS status. More research in the management of PJS is needed.